CONFIRMATION OF RESISTANCE IN WHEAT GERMPLASMS AGAINST STRIPE/YELLOW RUST THROUGH SEEDLING RESISTANCE TEST (SRT) AND ADULT PLANT RESISTANCE (APR) - ELANGBAM PREMABATI DEVI; DEEPSHIKHA; BIMLA KUMARI (The Bioscan, 2015)
In the present study, nine hundred and eighty wheat germplasm accessions of exotic collection of NBPGR were screened against stripe rust in 2012-13 seasons under natural condition. Out of these, 30 accessions showing resistance response were randomly selected with the aim of studying that to screen wheat germplasm accessions against yellow rust at seedling resistance test (SRT) and adult plant resistance (APR) during 2013-2014 seasons. During the study, results revealed that 8 accessions viz. EC-635612, EC-635627, EC-635881, EC-664208, EC- 664244, EC-692246, EC-693271 and EC-693322 were resistant towards all the tested pathotypes of stripe rust in seedling as well as at adult plant stage. Remaining 19 germplasms showed adult plant resistance response except 3 germplasms, i.e. EC-636264, EC-635861 and EC-664299. Additionally, the relationship between the plot yield and A-value of all the thirty germplasm accessions were also observed and was found to be negatively correlated with highly significant level (r = -0.603**). Present study suggests that out of 30 accessions, 27 wheat germplasm accessions were having resistance response that could be used for further incorporation in breeding programmes for developing stripe rust resistant wheat varieties.